2000
DOI: 10.1592/phco.20.7.644.35167
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Citrate for the Treatment of Apnea of Prematurity: A Double‐Blind, Placebo‐Controlled Study

Abstract: Caffeine citrate 10 mg/kg caffeine base (equivalent to 20 mg/kg caffeine citrate) intravenously followed by 2.5 mg/kg/day caffeine base (equivalent to 5 mg/kg/day caffeine citrate) either intravenously or orally for 10 days is safe and effective for treating apnea of prematurity in infants 28-32 weeks postconception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
1
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 28 publications
3
104
1
3
Order By: Relevance
“…10 The median birth weight for all the patients treated with aminophylline was 1 400 g and those treated with caffeine was 1 600 g. The incidence of AOP in this patient population is 25%. 11 Both these parameters in the two study arms were comparable.…”
Section: Discussionmentioning
confidence: 85%
“…10 The median birth weight for all the patients treated with aminophylline was 1 400 g and those treated with caffeine was 1 600 g. The incidence of AOP in this patient population is 25%. 11 Both these parameters in the two study arms were comparable.…”
Section: Discussionmentioning
confidence: 85%
“…70 Multiple clinical trials have shown that both caffeine and theophylline are effective treatment for AOP. [71][72][73][74] Initially theophylline was the standard therapy and it required close monitoring of serum levels. Since Food and Drug Administration approval of caffeine, theophylline has been largely replaced by caffeine as the first line of management.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Advances in neonatal care in recent decades have resulted in an increased survival rate in low-birth-weight premature infants. Therefore, the number of newborns with this disorder is increasing (Erenberg & Allen, 2000).…”
Section: Is Caffiene a Risk For Op? 49mentioning
confidence: 99%